Long-lasting tuberculous pleurisy. Issue 5 (25th May 2017) - Petruccioli, Elisa; Scriba, Thomas J.; Petrone, Linda; Hatherill, Mark; Cirillo, Daniela M.; Joosten, Simone A.; Codecasa, Luigi R.; Ottenhoff, Tom H.; Denkinger, Claudia M.; Goletti, Delia
We read with interest the correspondence from L. Ampollini and colleagues, in which they report the case of an immunocompetent patient who originally presented with pulmonary and extra-pulmonary tuberculosis (TB) at 33 years of age and which was thought to have persisted over many years. However, based on the clinical story described, we doubt that the patient had reactivation of TB at 65 years of age, when he presented with chest pain and dyspnoea and a computerised tomography (CT)-scan showed a calcifying pleurisy leading to a contralateral mediastinal shift and lung atelectasis. Mycobacterium tuberculosis was not isolated from the pleural effusion. Rather, a positive culture of Streptococcus was obtained and the patient was treated successfully with an anti-streptococcal therapy that was not TB-specific (amoxicillin/clavulanic acid for 3 weeks), with no sign of a TB relapse at follow up 2 years later. Therefore, it seems likely that L. Ampollini and colleagues are describing a case of bacterial pleuritis occurring in a patient with previous TB and calcified sequaele. It is necessary to find better tools to predict and monitor TB treatment outcomes and potential for reactivation http://ow.ly/CBxr30aLdCE